Sustained Release Drug Delivery Applications of Polyurethanes - Michael B. Lowinger; Stephanie E. Barrett; Feng Zhang; Robert O. Williams (MDPI AG, 2018)
Since their introduction over 50 years ago, polyurethanes have been applied to nearly every industry. This review describes applications of polyurethanes to the development of modified release drug delivery. Although drug delivery research leveraging polyurethanes has been ongoing for decades, there has been renewed and substantial interest in the field in recent years. The chemistry of polyurethanes and the mechanisms of drug release from sustained release dosage forms are briefly reviewed. Studies to assess the impact of intrinsic drug properties on release from polyurethane-based formulations are considered. The impact of hydrophilic water swelling polyurethanes on drug diffusivity and release rate is discussed. The role of pore formers in modulating drug release rate is examined. Finally, the value of assessing mechanical properties of the dosage form and approaches taken in the literature are described.